Líquen escleroso vulvar: comparações das terapias de fotobiomodulação, fotodinâmica e corticosteróide tópico avaliação histopatológica, imunohistoquímica e clínica- estudo fase II - Belotto, Renata Aparecida (2018)
Vulvar Lichen Sclerosus (VLS) is a non-neoplastic, non-infectious, chronic inflammatory dermatosis by unknown etiology that causes intense pruritus and genital stenosis. VLS can hinder the evacuation and urination, limiting the sexual life by pain and local trauma. At present, the gold standard treatment is the topical ultra-potent steroids to decrease clinical symptoms, even though they may cause several side effects. The literature indicates to chronic dermatosis that Photodynamic therapy (PDT) and Photobiomodulation Therapy (PBMT) are efficient treatments, which promote an effective anti-inflammatory and immunomodulatory effects, such as VLS. The aim of this study was to evaluate and compare PDT, PBMT and topical Corticosteroid (CG) responses in VLS by clinical (pruritus), histological and immunohistochemical responses. A prospective, randomized, controlled clinical study in VLS diagnosed by 36 patients at the Pérola Byington Hospital was performed. Twelve women, into 3 groups, were allocated: Steroid, PBMT and PDT Groups. Histological slides, according to Robboy's classification, pre and post treatment were studied. Immunohistochemical analysis by P53, Ki67, Cytokeratins 10 and 14, CD 34 and Laminin markers, as well as Mast cells (anti- inflammatory response) were verified. Statistical analyzes among groups evaluation by significant statistically (p< 0,05) were presented. Histological pattern changed from L2 to L1 in all treatments. Hydropic degeneration, hyperkeratosis and collagen hyalinization exhibited diminution post treatments. All therapies reduced the inflammatory process, CG in 58%, PDTG in 30% and TPBMG in 66.7%. Mast cells indicated reduction in all groups (p= 0.405). P53 and Ki 67 underwent changes after treatments, p = 0.405 and p = 0.841, respectively. CK10 and CK14 increased with p= 0.638 and p= 0.838, respectively. Laminin increased post treatments (p= 0.251). CD34 showed post-treatment change (p= 0.405). Pruritus reduced in all groups studied. Recurrences varied according to groups: CG recurred in 60%, PDTG in 36.3% and TPBMG in 63.6%. The photonic therapy seems to be a significant management while compared to steroid therapy as result of its side-effect, when applied for long periods. In this study, the vulvar pruritus and the skin phototype (Fitzpatrick) signalized their significant recurrence. Photonic therapies are promising, even though some multicentric studies should be carry out, by a larger casuistic for establishing reliable protocols.